1988
DOI: 10.1126/science.2833817
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine Triphosphatase Activating Protein (GAP) Interacts with the p21 ras Effector Binding Domain

Abstract: A cytoplasmic protein that greatly enhances the guanosine triphosphatase (GTPase) activity of N-ras protein but does not affect the activity of oncogenic ras mutants has been recently described. This protein (GAP) is shown here to be ubiquitous in higher eukaryotes and to interact with H-ras as well as with N-ras proteins. To identify the region of ras p21 with which GAP interacts, 21 H-ras mutant proteins were purified and tested for their ability to undergo stimulation of GTPase activity by GAP. Mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
264
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(273 citation statements)
references
References 16 publications
6
264
0
1
Order By: Relevance
“…Although p120 GAP and NF1/neuro®bromin clearly function as negative regulators of Ras function (Boguski and McCormick, 1993), p120 GAP represented the ®rst candidate Ras e ector (Adari et al, 1988;Cale s et al, 1988). Apparent evidence against an e ector function for Ras GAPs came from studies of Ras e ector domain mutants that impaired p120 or NF1 interactions, yet retained strong focus-forming activity (Marshall and Hettich, 1993).…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 99%
“…Although p120 GAP and NF1/neuro®bromin clearly function as negative regulators of Ras function (Boguski and McCormick, 1993), p120 GAP represented the ®rst candidate Ras e ector (Adari et al, 1988;Cale s et al, 1988). Apparent evidence against an e ector function for Ras GAPs came from studies of Ras e ector domain mutants that impaired p120 or NF1 interactions, yet retained strong focus-forming activity (Marshall and Hettich, 1993).…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 99%
“…This protein appears to be involved in growth control and it has been proposed to function not only as the negative regulator of the ras-p21, but also as its downstream effector [39]. Recently, it has been reported that compounds such as arachidonic acid and phosphatidic acid are able to inhibit GAP activity [40].…”
Section: Inhibition Of Gap Activity By Lysolipidsmentioning
confidence: 99%
“…The low intrinsic GTPase activity of p21'"'is enhanced by a GTPaseactivating protein (Trahey and McCormick, 1987). Several point mutations in the switch 1 region were reported to destroy the transforming activity of oncogenically activated forms of p2Iri'', which indicated that this part of the protein may constitute the location which regulates the GTPase activity (McCormick, 1989;CalCs et al, 1988;Adari et al, 1988;Sigal et al, 1986). In the a-subunit of heterotrimeric G proteins, where the switch I region was also identified, the role of GTPase-activating protein is apparently fulfilled by a covalently integrated domain (Markby et al, 1993).…”
mentioning
confidence: 99%